2020
DOI: 10.4041/kjod.2020.50.5.314
|View full text |Cite
|
Sign up to set email alerts
|

Short-term treatment effects produced by rapid maxillary expansion evaluated with computed tomography: A systematic review with meta-analysis

Abstract: Objective To identify the available evidence on the effects of rapid maxillary expansion (RME) with three-dimensional imaging and provide meta-analytic data from studies assessing the outcomes using computed tomography. Methods Eleven electronic databases were searched, and prospective case series were selected. Two authors screened all titles and abstracts and assessed full texts of the remaining articles. Seventeen case series were included in the quantitative synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Relapse is always inevitable although significantly improved mid-palatal suture width is acquired after expansion and a long maintenance period. A recent systematic review reported that at least 10% post-retention relapse occurred [ 46 ]. The reason is that a malformed balance with the dental arch, tongue and buccal muscles already exists before expansion and the newly formed mid-palatal sutures subjected to compressive force from the buccal-inclined upper posterior tooth, the lingual-inclined lower posterior tooth, the relatively small tongue or the nervous buccal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Relapse is always inevitable although significantly improved mid-palatal suture width is acquired after expansion and a long maintenance period. A recent systematic review reported that at least 10% post-retention relapse occurred [ 46 ]. The reason is that a malformed balance with the dental arch, tongue and buccal muscles already exists before expansion and the newly formed mid-palatal sutures subjected to compressive force from the buccal-inclined upper posterior tooth, the lingual-inclined lower posterior tooth, the relatively small tongue or the nervous buccal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Palatal interalveolar length (PIL), palatal arch depth (PAD) and maxillopalatal arch angle (MPAA) were measured based on the criteria of Kajan et al [ 9 ]. The radiographic landmarks used for the determination of PIL, PAD and MPAA are described in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is a scarcity of radiographic studies evaluating the palatal dimensions of subjects with CB, TH and NSD. The evaluation of the palatal dimensions and nasal structures is important from a clinical aspect, as procedures such as rapid maxillary expansion (RME) have a significant effect on nasal structures [ 9 ]. With this background, we conducted a study to determine the effect of CB and NSD on the dimensions of the hard palate using CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid maxillary expansion (RME) is the treatment of choice for the correction of transversal maxillary deficiency and posterior cross-bite in growing subjects [1]. This treatment is generally performed using a tooth-anchored maxillary expander device [2].…”
Section: Introductionmentioning
confidence: 99%